OMEGA-3 Fatty Acids Retention, Oxidative Quality, and Sensoric Acceptability of Spray-Dried Flaxseed Oil - Muhammad Zia Shahid; Muhammad Imran; Muhammad Kamran Khan; Muhammad Haseeb Ahmad; Muhammad Nadeem; Niaz Muhammad; Adeela Yasmin (Journal of Food Quality)
Flaxseed is naturally a rich source of essential omega-3 fatty acid, α-linolenic acid (ALA), which exhibits nearly 57% of its entire fatty acid profile. Oxidation of omega-3 fatty acids during processing and storage results in reduced shelf stability of food products and limited health potentials. Spray-drying is considered a processing technique to shield omega-3 fatty acids from oxidative damage. For the purpose, the extracted flaxseed oil (FSO) together with the emulsifier (flaxseed meal polysaccharide gum) was passed through a mini spray-dryer to prepare spray-dried flaxseed oil (SDFSO) samples. The SDFSO samples for quality were evaluated at 0th, 30th, and 60th days of storage at two different temperatures of 4°C and 25°C, accordingly. The maximum oil protection efficiency was recorded as 90.78% at 160°C. The highest percentage for ALA retention was recorded as 54.7% and 53.9% at 4°C, while the lowest retention was observed as 48.6% and 46.2% at 25°C after 30 and 60 days of storage, respectively. The inlet (160°C) and outlet air temperatures (80°C) were considered as key factors contributing a decline in retention of ALA of the SDFSO samples. The free fatty acid contents of FSO and SDFSO samples reached to their peaks, i.e., 1.22% and 0.75%, respectively, after 60 days of storage at 25°C. The initial peroxide value of FSO (control) was 0.16, which increased to 0.34 (4°C) and 1.10 (25°C) meq/kg O2 at the end of 60 days storage. The value for malondialdehyde of SDFSO samples was increased from 0.17 (0 day) to 0.34 nmol/g of lipids at 60 days (4°C), and the same increasing trend was observed at 25°C. In the case of color and overall acceptability, the lowest evaluation scores were awarded to FSO samples in comparison to SDFSO samples. Overall, SDFSO possessed improved oxidative quality and can be recommended as a fortifying agent in various functional food products.